NILAI KARAKTER GOTONG ROYONG DALAM TRADISI BEJOPAI PADA MASYARAKAT DESA TANAH MERAH DUSUN BANGAU KECAMATAN KAYAN HULU KABUPATEN SINTANG - Fusnika, Fusnika; Purnomo, Sapto; Andela, Rivaldi (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2022)
This research was about how the Bejopai tradition in the Tanah Merah village community, the stages in the Bejopai tradition, and the character values work together in the Bejopai tradition. This study aims to describe the Bejopai tradition, the stages in the Bejopai tradition, and the value of the gotong royong character in the Bejopai tradition. This research uses qualitative methods with descriptive qualitative research. Data collection techniques using direct observation techniques, interviews, and documentation. Data collection tools using observation sheets, interview guides, and document guides. The study results show that: 1) The Bejopai tradition in the Tanah Merah village community has existed since the ancestors' time and is carried out regularly once a year. Usually carried out from the sixth month to the last, namely manyi. Every year it is always carried out in the Bejopai tradition. 2) The stages in the Bejopai tradition are still very thick and often carried out by carrying out stages such as montap, nobas, nobang, nunu, manog, nugal, mabau, manyi, and ngirik padi, so that the Bejopai tradition can be carried out properly without reducing step by step. Step. 3) The character values contained in the bejopai tradition are responsibility, help, justice and unity, togetherness, kinship, volunteering, and the active role of each individual. With mutual cooperation, it will be easier for the community to carry out the Bejopai tradition so that the Bejopai tradition will always be preserved from time to time, generation to generation, and uphold the value of art, culture, or tradition. Carry out cooperation activities, especially in the Bejopai tradition, in the form of the public and individual interests. In addition, the community must interpret the values of cooperation in the Bejopai tradition as a form of togetherness in neighborly life to lighten the workload of each other to make time efficient to achieve more optimal output or results.Â Keywords: Character Value of Gotong Royong, Bejopai Tradition.